ANALISIS IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS ISEQ DALAM MEWUJUDKAN GENERASI INDONESIA EMAS 2045 DI SEKOLAH DASAR - Aidah, Ai; Pujiasti, Dea Asri; Febrianti, Fitri Ayu; Aliyah, Leli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In the midst of the nation’s moral bankruptcy, rampant acts of violence, politicians’ incoherence regarding political rhetoric and daily educational behavior. With character education implemented systematically and continuously, students will become intellectually, spiritually and emotionally intelligent (Kasrani, 2018). Intelligences are important provisions for students in preparing for the future, because someone will more easily and successfully face all kinds of life challenges, including, the challenge of realizing a Golden Indonesia 2045 (Inevianti, 2018). Based on the statement above, efforts that can be made to create a golden Indonesia generation in 2045 are by implementing ISEQ-based character education. ISEQ-based character education is a combined education system of several intelligence characters, namely intellectual intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ) (Triyono, 2016). This research aims to find out what kind of implementation is being carried out at SDIT Al Mashduqi in a effort to create a golden Indonesia generation in 2045. This research uses qualitative research methods. Qualitative research is research that is descriptive and tends to use analysis. The data collection technique used in this research was triangulation (combined), namely by observation and interviews. The results of this research explain that the implementation carried out by schools in improving the there ISEQ-based intelligences in the effort to realize a Golden Indonesia in 2045 has been very good. This can be seen from the school’s thoroughness in teaching each lesson to its students using several methdos, programs implemented by the school and the school’s concerm for its students by holding parent meetings of students involving psychologists.